1978
DOI: 10.1007/bf01869043
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and glutamic acid uptake by rat renal brushborder membrane vesicles

Abstract: Glutamine uptake by rat renal brushborder vesicles occurred via two distinct saturable processes with Km values of 0.145 and 8.5 mM which were stimulated by both ionic and sodium gradients with a pH optimum of 6.8--7.1. Glutamic acid uptake also occurred by a two-component system with Km values of 0.016 and 3.60 mM. Both components were stimulated specifically by a sodium gradient. The low Km system for glutamic acid had a pH optimum of 7.2--7.4. Glutamine entry at 0.06 mM was inhibited by a variety of amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…oxidation of the carbon skeleton by mitochondria may be inhibited [4,26]. Our results with isolated tubule segments confirm the findings with cor tical suspensions [12], and renal cortical slices [7], The decline in oxidation at alkalotic pH can also be due to reduced uptake [18], but one must consider the same limitations on the relationship between oxidation and uptake as discussed for acidosis. The restriction of the effect of pH to the proximal tubule is similar to the observations of Good and Burg[l] regard ing ammonia production during metabolic acidosis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…oxidation of the carbon skeleton by mitochondria may be inhibited [4,26]. Our results with isolated tubule segments confirm the findings with cor tical suspensions [12], and renal cortical slices [7], The decline in oxidation at alkalotic pH can also be due to reduced uptake [18], but one must consider the same limitations on the relationship between oxidation and uptake as discussed for acidosis. The restriction of the effect of pH to the proximal tubule is similar to the observations of Good and Burg[l] regard ing ammonia production during metabolic acidosis.…”
Section: Discussionsupporting
confidence: 80%
“…We have observed an increased oxidation rate at moderate acidotic levels that was not sustained during severe acidosis. The latter change may be due to a relative decline in glutamine uptake at pH levels below the optimal value [18]. Such a decline, however, would have to be extreme as the saturation of oxidation is significantly below the Km for up take.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a lower concentration of glutamic acid, however, Weiss et al 9 ) found that glutamic acid (0.06 mM) uptake exhibited a Na + -dependent overshoot phenomenon of The Na + -dependent uptake of each amino acid was obtained by subtracting the uptake in the KCI medium from that in the NaCI medium. For the urinary excretion of free amino acids, the values represent the means for four rats and the vertical bars indicate the standard error.…”
Section: Resultsmentioning
confidence: 99%
“…Cortical slices were made with a Stadie-Riggs microtome and the tissue weighed. Brushborder membrane vesicles were then prepared using the method of Booth and Kenny (2) modified as described by Weiss et al (21). The final membrane pellet was suspended in T H M buffer, pH 7.4 (2 mM Tris/HEPES + 100 mM mannitol) to a protein concentration of 0.3-0.4 mg/ml as determined by the method of Lowry et al (13).…”
Section: Animalsmentioning
confidence: 99%